Asymmetric synthesis of pyrrolidine-containing chemical scaffolds via Tsuji-Trost allylation of N-tert-butanesulfinyl imines - Dawood, Rafid S.; Georgiou, Irene; Wilkie, Ross P.; Lewis, William; Stockman, Robert A. (Wiley-VCH Verlag, 2017)
A simple and efficient asymmetric synthesis of novel sp3 rich pyrrolidine chemical scaffolds over five steps starting from simple ketones is described. Key steps involve the use of tert-butanesulfinamide as a chiral auxiliary to perform an asymmetric Tsuji-Trost allylation, with subsequent cross-metathesis with an acrylate ester and reduction of the sulfinimine/cyclisation of the resulting amine giving the pyrrolidine scaffolds in high yields and diastereoselectivites. By removing the chiral auxiliary and functionalising the ester group, the resulting scaffold core can be further derivatised.